Leonurine as a dietary compound: Its role in ferroptosis inhibition through Nrf2 signaling pathway activation - Qi, Le; Zhu, Lili (Italian Journal of Food Science, 2024)
This research explores the potential of leonurine, a component found in motherwort, to inhibit intestinal inflammatory response in patients of inflammatory bowel disease (IBD) through dietary means with a particular emphasis on how it influences the nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathway. Using colon epithelial cell lines, HT29 and Caco-2, we set up models to study the impact of inflammation, oxidative stress, and apoptosis induced by lipopolysaccharide (LPS). In addition, we employed Nrf2 knockout cell lines to understand its function in a better way. The introduction of leonurine is aimed to evaluate its ability to reduce cell damage and inflammatory reactions by activating the Nrf2–heme oxygenase-1 (HO-1) pathway. Results indicated that LPS exposure led to inflammation, oxidative stress, apoptosis, and potential ferroptosis. It was observed that Nrf2 acted as a suppressor in this scenario; its absence increased cell susceptibility to these challenges. Treatment with leonurine notably decreased inflammation, oxidative stress, and apoptosis; however, these protective effects were significantly reduced in cells lacking Nrf2. This confirms that leonurine can inhibit oxidative stress, inflammatory response, apoptosis, and potential ferroptosis mechanism of colon epithelial cells by activating Nrf2. This study not only enhances our understanding of how leonurine regulates IBD but also highlights the importance of Nrf2 by shedding light on IBD development and potential nutritional approaches for its management.